Analisis Termal Stainless Steel Ice Cubes dengan Menggunakan Sensor Termokopel DS18B20 Berbasis Arduino - Luthfi Luthfi (Jurnal Teknologi, 2023)
Stainless ice cubes as reusable ice packs have recently become more popular for cooling food and beverages. Compared to ordinary water-based ice cubes, they will not alter the taste as they do not melt and mix with food/drink, and in the long run, they can save money as they can be reused. Due to little information on their technical performance in the literature, this study will investigate their thermal characteristics, especially when compared to water ice cubes and custom-made stainless ice cubes. A water-proved temperature measurement system consisting of 5 pieces of DS18B20 thermocouple sensor controlled by Arduino UNO DIP Microcontroller was built and tested for this purpose. The tests were conducted on three separate drinking glasses containing three different ice cubes. The measurement system successfully revealed the temperature evolution of the three types of ice cubes. Water ice cubes still produced the coldest water temperature, although the commercial ice cubes purchased from the online market are not too far behind. Custom-made ice cubes containing no Phase Change Material (PCM) substance inside them do not significantly cool the water.